Dante's Heavenly Rose: An Analogue or a Borrowing? - Silverstein, Theodore (Harvard theological review, 1949)
The figure of the rose with which Dante tops the soaring structure of his Paradiso may seem to have stimulated comment enough by now, and the present note, pointing out yet another possible analogue, serve merely to expand the raw bulk of such materials, which, though interesting in themselves, add little essential to our knowledge of the poem. But no Stoffkritik has yet explained entirely happily to the student of the popular otherworld traditions, the origin of this figure in the Divine Comedy or the peculiar fitness of its use there. And the present parallel has the virtue that it is really a parallel, and not confined to the rose alone, whose figure and symbolic significance are common property in the Middle Ages. On the contrary, it describes at the supernal heights of heaven a city which is shaped like a rose, is also the special paradise of the Virgin, and contains traces of another motif — the empty thrones and the waiting crowns and vestments reserved until the Time shall come for the just and the poor in spirit —, which Dante also places for the elect within the limits of this heavenly city. All this, moreover, appears in a work belonging to that body of otherworld lore from which the Divine Comedy, itself the most elaborate literary example of this genre, frequently borrows.